A Summer Break for the Unemployment Rate: Google-Assisted Forecasting Signals Easing - Nikos Askitas; Klaus F. Zimmermann (Weekly Report, 2009)
To date, the Great Recession has only had a mild impact on the German labor market. In view of the uncertainties surrounding future economic growth, the low utilization of the workforce in firms, and the prevalence of working hour reductions, many observers are anticipating a dramatic rise in unemployment in the fall, with the total number of unemployed rapidly surpassing the four-million mark. Yet according to forecasts based on Google search statistics, in all likelihood the unemployment rate will remain relatively stable in August and through the end of September, when elections for the German Bundestag will be held. The seasonally adjusted unemployment rate is actually falling. Given this fact, the danger that the total number of unemployed will exceed four million during this year seems increasingly unlikely.
Keywords: C22; C82; E17; E24; E37; 330; Google; Internet; Keyword search; Search engine; Unemployment; Predictions